EXPLICIT FACTORIZATION OF A (P,Q)-CIRCULANT MATRIX-FUNCTIONS - Topikyan, G.M. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
The paper considers a factorization problem of a matrix-function, obtained from a circulant by a right and left multiplication by diagonal rational matrixfunctions. Formulas for partial indices are obtained by means of ranks of a finite number of explicit type matrices. A factorization construction of this matrixfunction based on factorization of finite number of functions is given as well.